2017
DOI: 10.4172/2472-1212.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Ceragenins as Mimics of Endogenous Antimicrobial Peptides

Abstract: Ceragenins are small molecule mimics of endogenous antimicrobial peptides (AMPs), and as such display broadspectrum antimicrobial activity. These molecules are derived from a common bile acid and can be prepared at a large scale. Because ceragenins are not peptide based, they are not substrates for proteases. Gram-negative and positive bacteria are susceptible to ceragenins, including drug resistant organisms. Although ceragenins and colistin have common features, ceragenins retain full antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 110 publications
(116 reference statements)
1
27
0
Order By: Relevance
“…The combination could also be considered in the development of products for wound healing for topical applications. Ceragenins, with their: (i) strong antimicrobial activity against a variety of microorganisms, even Bacillus spores, (ii) ability to inhibit biofilm formation, (iii) biological activity in body fluids, (iv) good safety profile, and (v) anti-inflammatory properties, could be excellent candidates for potential use also in such infections as endophthalmitis [39]. Endophthalmitis following ocular trauma can be caused by a wide range of bacteria and fungi, including multidrug-resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The combination could also be considered in the development of products for wound healing for topical applications. Ceragenins, with their: (i) strong antimicrobial activity against a variety of microorganisms, even Bacillus spores, (ii) ability to inhibit biofilm formation, (iii) biological activity in body fluids, (iv) good safety profile, and (v) anti-inflammatory properties, could be excellent candidates for potential use also in such infections as endophthalmitis [39]. Endophthalmitis following ocular trauma can be caused by a wide range of bacteria and fungi, including multidrug-resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that they are not peptide-based, they are not substrates for ubiquitous proteases. Preparation and purification of ceragenins on a large scale is relatively straightforward, they are stable under physiological conditions and even long-term storage in solution does not reduce their antibiotic activities [37,38]. As ceragenins follow the amphiphilic structure of AMPs they display a similar spectrum of activity against bacterial, fungi and lipid-enveloped viruses [39].…”
Section: Structure and Mechanism Of Action Of Ampsmentioning
confidence: 99%
“…Ceragenins and AMPs, on the other hand, target the bacterial membrane, and are able to kill bacterial and fungal cells regardless of whether they are rapidly growing, dividing, or sessile [83]. In addition, the relatively small size of ceragenins allows them to penetrate the extracellular matrix of biofilms and gain access to the cells within [38]. A comparative study of ceragenins with ciprofloxacin indicated that a much lower concentration of CSA-13 was required to eradicate an established biofilm consisting of a meticillin-resistant strain of S. aureus in comparison with ciprofloxacin.…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…Although they possess diverse structures, most AMPs share common characteristics such as short amino acids and positive charges (Li et al, ). AMPs are also known as compounds with broad‐spectrum antimicrobial activity against gram‐negative and gram‐positive bacteria, fungi, and lipid‐enveloped viruses (Hashemi, Holden, Durnas, Bucki, & Savage, ). Furthermore, they retain activity against antibiotic‐resistant strains and do not readily elicit resistance (Brogden & Brogden, ).…”
Section: Introductionmentioning
confidence: 99%
“…gram-positive bacteria, fungi, and lipid-enveloped viruses (Hashemi, Holden, Durnas, Bucki, & Savage, 2017). Furthermore, they retain activity against antibiotic-resistant strains and do not readily elicit resistance (Brogden & Brogden, 2011).…”
mentioning
confidence: 99%